EVALUASI DAN PENILAIAN PELATIHAN JABATAN - Moeheriono, Moeheriono (FIA UB, 2007)
Leadership Training Course Level III (DIKLATPIM TINGKAT III) indirectly affects employee welfare through employee competency, and career, and it indirectly affects institutional performance through work motivation and employee performance. Moreover, it is also found that Leadership Training Course Level III (DIKLATPIM TINGKA T III) does not have a direct effect on employee career; but rather it affects employee career through competency. And, Leadership Training Course Level III (DIKLA TPJM TINGKA T III) does not have a direct effect on employee performance, but rather it affects employee performance through motivation. Other additional findings are also reported and further discussed, while several recommendations for future researchh are developed.Keywords: employee competency career, employee welfare, works motivation, employee performance and institutional performance.